Checklist, typification details, and nomenclature status of Basidiomycota, originally described from Sri Lanka - Karunarathna, Samantha C.; Priyashantha, A.k Hasith; Tibpromma, Saowaluck; Galappaththi, Mahesh C. A.; Premarathne, Bhagya M.; Wijayawardene, Nalin N.; Wimalasena, Madhara K.; Jayalal, R.g. Udeni; Wickramanayake, Kawmini D.; Dangalla, Hasanka; Jayathunga, W. Hashini; Brahmanage, Rashika S.; et al. (Phytotaxa, 2023)
Sri Lanka is considered a mega-biodiversity hotspot, with a rich collection of flora and fauna. Basidiomycota is the second largest and most diverse phylum of fungi, comprising over 31,000 species. The present paper is intended to bring together all reported species with their typification details and updated/current nomenclature status of basidiomycetes in Sri Lanka. The checklist consists of 725 species belonging to a total of 138 genera. The genus Agaricus is represented by the highest number of species (169), followed by Marasmius (62), Polyporus (53), Uredo (49), Corticium (27), Hygrophorus (20), Thelephora (15), Lentinus (15), Hydnum (12), Hymenochaete (11), Poria (11), Clavaria (10), and Puccinia (10). All other genera constitute less than 10 species, whereas 72 of the other genera contain one species each.